Magnetically directed co-nanoinitiators for cross-linking adhesives and enhancing mechanical properties - Kongcharoen, Haruethai (2022)
Magnetically directed localized polymerization is of immense interest for its extensive impacts and applications in numerous fields. The use of means untethered from an external magnetic field to localize initiation of polymerization to develop a curing system is a novel concept, with a sustainable, efficient, and eco-friendly approach and a wide range of potential in both science and engineering. However, the conventional means for the initiation of polymerization cannot define the desirable location of polymerization, which is often exacerbated by the poor temporal control in the curing system. Herein, the copper-immobilized dendrimer-based magnetic iron oxide silica (MNPs-G2@Cu2+) co-nanoinitiators are rationally designed as initiators for redox radical polymerization. The nanoinitiators are magnetically responsive and therefore enable localized polymerization using an external magnetic field. In this work, anaerobic polymerization of an adhesive composed of triethylene glycol dimethacrylate, tert-butyl peroxybenzoate, and MNPs-G2@Cu2+ as the magnetic co-nanoinitiators has been investigated. The use of a magnet locates and promotes redox free radical polymerization through the synergistic functions between peroxide and MNPs-G2@Cu2+ co-nanoinitiators. The mechanical properties of the resulting polymer are considerably reinforced because the MNPs-G2@Cu2+ co-nanoinitiators concurrently play another crucial role as nanofillers. This strategy provides a novel approach for magnetically tunable localized polymerization, which allows new opportunities to govern the formulation of advanced adhesives through polymerization under hazard-free conditions for various promising applications.